High-performance popcorn insole material and preparation method thereof

By combining bio-based compounds with silanized nanomaterials and mixing them with crosslinking agents and isocyanates, high-performance single-component polyurethane glue is prepared, and combined with popcorn particles, the existing popcorn insoles are solved, and better wear resistance, breathability and service life are achieved.

CN119752153AInactive Publication Date: 2025-04-04ZHONGSHAN FUXIANG SHOES MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510049648.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing popcorn insoles wear faster when they are frequently jumped or long walks, have a short service life, and are poor in breathability and water permeability, resulting in discomfort for wearers and accelerate material aging.

Method used

Modified bio-based polyols are obtained by combining the bio-based compounds with silanized nanomaterials to form a composite and combined with a crosslinking agent. The modified biomass polyol is then mixed with isocyanate, polycaprolactone triol, catalyst and antioxidant to prepare a one-component polyurethane glue. The glue is combined with popcorn particles to finally obtain a high-performance popcorn insole material.

Benefits of technology

It significantly improves the breathability, water permeability, wear resistance and mechanical properties of the insole, extends the service life, and improves the overall overall performance, while maintaining good environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a high-performance popcorn insole material and a preparation method thereof, and belongs to the technical field of polyurethane materials, the high-performance popcorn insole material comprises one-component polyurethane glue and popcorn particles; the single-component polyurethane glue is prepared from the following raw materials in parts by weight: 35 to 45 parts of modified bio-based polyol, 20 to 30 parts of polycaprolactone triol, 10 to 15 parts of a composite chain extender, 20 to 25 parts of isocyanate, 0.05 to 0.1 part of a catalyst and 1 to 3 parts of an antioxidant, according to the technical scheme, a bio-based compound is combined with a silanized nano material and then combined with a cross-linking agent, and modified bio-based polyol is obtained; isocyanate, the modified bio-based polyol, polycaprolactone triol, a catalyst and an antioxidant are mixed, and single-component polyurethane glue is obtained; the single-component polyurethane glue is combined with popcorn particles to obtain the high-performance popcorn insole material; the air permeability, the water permeability, the wear resistance and the mechanical property of the popcorn insole material are generally improved, and the environmental protection property is relatively good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane materials, and in particular relates to a high-performance popcorn insole material and a preparation method thereof. Background Art

[0002] As the demand for footwear on the market increases day by day, people's requirements for the comfort, wear resistance, resilience and other functions of insoles are also gradually increasing. Traditional insole materials often have certain limitations in terms of comfort, breathability and environmental protection, while popcorn insoles have been widely used in the production and manufacturing of insoles due to their superior resilience and good mechanical properties. Popcorn insoles are usually made of thermoplastic polyurethane elastomer (TPU) as the main raw material, and are treated by a special process under high temperature and high pressure to form a tiny closed-cell structure similar to popcorn inside. This unique structure not only gives the insole an extremely light weight, but also greatly improves its resilience and breathability, bringing a better comfort experience to the wearer. However, although this popcorn insole has shown significant advantages in many aspects, it still faces some challenges in practical applications.

[0003] In the prior art, although popcorn insoles have good resilience, frequent jumping or long-term walking may accelerate the wear of the insoles, resulting in a relatively short service life; and the existing popcorn insoles have poor air permeability and water permeability, and cannot effectively discharge sweat from the feet, which not only makes the wearer feel uncomfortable, but also accelerates the aging process of the insole material when in a humid environment for a long time, resulting in a decrease in the resilience, comfort, and mechanical properties of the insole material. Therefore, it is necessary to prepare a high-performance popcorn insole material with good air permeability, water permeability, wear resistance and mechanical properties. Summary of the invention

[0004] The purpose of the present invention is to provide a high-performance popcorn insole material and a preparation method thereof, wherein a composite material is obtained by combining a bio-based compound with a silanized nanomaterial; the bio-based compound is composed of a mixture of castor oil and vanillin, which can play a synergistic role and better improve the mechanical properties, wear resistance and durability of polyurethane; the silanized nanomaterial is prepared by combining a silane coupling agent with a nanomaterial; the nanomaterial is composed of a mixture of hollow nano titanium dioxide microspheres and nano silicon dioxide, which effectively improves the air permeability, water permeability, wear resistance and mechanical properties of polyurethane; the bio-based compound is combined with the silanized nanomaterial to form a mat The alkali structure is formed to enhance the network rigidity and cross-linking density of polyurethane; the complex is combined with a cross-linking agent to obtain a modified bio-based polyol; the reaction activity between the modified bio-based polyol and isocyanate is increased, and the cross-linking degree of polyurethane is increased; the composite chain extender is prepared by combining a rigid compound with ethanolamine; the bonding properties, mechanical properties, wear resistance, etc. of the single-component polyurethane glue are further enhanced; the single-component polyurethane glue is combined with popcorn particles to finally obtain a high-performance popcorn insole material, the binding force between the single-component polyurethane glue and the popcorn particles is strong, which generally improves the comprehensive performance of the high-performance popcorn insole material and has good environmental protection.

[0005] Technical problem to be solved by the present invention: In the prior art, although popcorn insoles have good resilience, frequent jumping or long-term walking may accelerate the wear of the insoles, resulting in a relatively short service life; and the existing popcorn insoles have poor air permeability and water permeability, and cannot effectively discharge sweat from the feet, which not only makes the wearer feel uncomfortable, but also accelerates the aging process of the insole material when in a humid environment for a long time, resulting in a decrease in the resilience, comfort, mechanical properties, etc. of the insole material, so it is necessary to prepare a high-performance popcorn insole material with good air permeability, water permeability, wear resistance and mechanical properties.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A high-performance popcorn insole material, comprising a single-component polyurethane glue and popcorn particles; The one-component polyurethane glue comprises the following raw materials in parts by weight: 35-45 parts of modified bio-based polyol, 20-30 parts of polycaprolactone triol, 10-15 parts of composite chain extender, 20-25 parts of isocyanate, 0.05-0.1 parts of catalyst and 1-3 parts of antioxidant; The method for preparing the modified bio-based polyol comprises the following steps: A1: Combining bio-based compounds with silanized nanomaterials to obtain composites; A2: Combining the complex with a cross-linking agent to obtain a modified bio-based polyol.

[0007] Furthermore, step A1 is specifically as follows: The bio-based compound is added to ethanol to obtain solution A, the silanized nanomaterial is added to ethanol to obtain solution B, solution B is added to solution A, and then stirred and reacted at 45-55°C for 7-9h. After the reaction is completed, it is cooled to room temperature, filtered, washed with ethanol, and vacuum dried at 60-70°C to obtain a composite.

[0008] In the above reaction process, the bio-based compound has an aldehyde group and the silylated nanomaterial has an amino group. The aldehyde group in the bio-based compound can combine with the amino group in the silylated nanomaterial, and the silylated nanomaterial and the bio-based compound are combined to obtain a composite.

[0009] Furthermore, the mass ratio of the bio-based compound to ethanol is 0.8-1.2:30-40.

[0010] Furthermore, the bio-based compound is composed of castor oil and vanillin mixed in a mass ratio of 1-1.2:0.6-0.7.

[0011] Furthermore, the mass ratio of the silanized nanomaterial to ethanol is 0.9-1.1:25-35.

[0012] Furthermore, the method for preparing the silanized nanomaterial comprises the following steps: Mix ethanol and deionized water, add silane coupling agent, and stir evenly, then add acetic acid and stir until the pH value of the solution reaches 3-4, then perform ultrasonic treatment for 25-35 minutes, add nanomaterials, stir and react at 50-55°C for 11-13 hours, after the reaction is completed, wash with ethanol, and dry at 50-60°C for 4-6 hours to obtain silanized nanomaterials.

[0013] In the above reaction process, the silane coupling agent is hydrolyzed to produce silanol groups. The nanomaterial has hydroxyl groups. The silanol groups in the silane coupling agent can react and combine with the hydroxyl groups in the nanomaterial, so that the silane coupling agent is grafted onto the nanomaterial to finally obtain the silanized nanomaterial.

[0014] Furthermore, the mass ratio of the ethanol, deionized water and silane coupling agent is 70-75:8-12:19-21.

[0015] Furthermore, the silane coupling agent is composed of a mixture of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 3-isocyanatepropyltriethoxysilane in a mass ratio of 0.8-0.9:0.4-0.5.

[0016] Furthermore, the nano material is composed of a mixture of hollow nano titanium dioxide microspheres and nano silicon dioxide in a mass ratio of 0.9-1.1:0.5-0.6.

[0017] Furthermore, the preparation method of the hollow nano titanium dioxide microspheres comprises the following steps: Add potassium chloride aqueous solution to ethanol, then add butyl titanate, stir for 10-15 minutes, let stand at room temperature for 20-24 hours, wash with anhydrous ethanol and deionized water in turn, and dry at 40-50°C to obtain solid nano titanium dioxide. Add solid nano titanium dioxide and ammonium fluoride to deionized water, stir evenly, react at 175-185°C for 11-13 hours, filter, wash with anhydrous ethanol and deionized water in turn, and finally dry at 40-50°C to obtain hollow nano titanium dioxide microspheres.

[0018] Furthermore, the mass ratio of the potassium chloride aqueous solution, ethanol, and butyl titanate is 3-5:95-100:2.3-2.7.

[0019] Furthermore, the mass ratio of the solid nano-titanium dioxide, ammonium fluoride and deionized water is 0.2-0.25: 0.08-0.12: 35-40.

[0020] Furthermore, step A2 is specifically as follows: The complex is mixed with a cross-linking agent, and a photoinitiator is added and stirred evenly. The mixture is then irradiated with ultraviolet light from a mercury lamp in an ice water bath for 1-2 hours. After the irradiation, ethyl acetate is added for dilution, and the mixture is washed with deionized water and a saturated sodium chloride solution in sequence, and then dried with magnesium sulfate. The ethyl acetate is removed by rotary evaporation, and finally vacuum dried at 50-60°C to obtain a modified bio-based polyol.

[0021] In the above reaction process, the complex has a carbon-carbon double bond and the cross-linking agent has a thiol group. Under the action of the photoinitiator, the carbon-carbon double bond in the complex can combine with the thiol group in the cross-linking agent through a thiol-thiol click reaction, thereby combining the cross-linking agent and the complex together to finally obtain a modified bio-based polyol.

[0022] Furthermore, the mass ratio of the composite, the cross-linking agent and the photoinitiator is 0.8-1.2:2.8-3.2:0.03-0.05.

[0023] Furthermore, the cross-linking agent is composed of 1-thioglycerol and 6-mercapto-1-hexanol mixed in a mass ratio of 0.8-0.9:0.3-0.4.

[0024] Furthermore, the photoinitiator is photoinitiator 1173 or photoinitiator 651.

[0025] Furthermore, the preparation method of the one-component polyurethane glue comprises the following steps: Weigh the raw materials by mass, put the modified bio-based polyol, polycaprolactone triol and composite chain extender into the reaction kettle, heat to 120-130°C, vacuum dehydrate under stirring, then cool to 70-80°C, add isocyanate, react at 70-80°C for 2-3h, add catalyst and antioxidant under nitrogen protection, continue to react at 70-80°C for 0.5-1.5h, vacuum degassing until no bubbles appear, discharge the material, and obtain a one-component polyurethane glue.

[0026] Furthermore, the isocyanate is a mixture of isophorone diisocyanate, triphenylmethane triisocyanate and 4,4-diisocyanate dicyclohexylmethane in a mass ratio of 1-1.2:0.6-0.7:0.2-0.3.

[0027] Furthermore, the catalyst is dibutyltin dilaurate or stannous isooctanoate.

[0028] Furthermore, the antioxidant is at least one of antioxidant 1076, antioxidant 168, and antioxidant 1010.

[0029] Furthermore, the preparation method of the composite chain extender comprises the following steps: The rigid compound is added to methanol, and then ethanolamine is added, and then the reaction is stirred at 45-55°C for 7-9 hours. After the reaction is completed, the methanol is removed by rotary evaporation, washed with acetone, filtered, and finally dried at 70-80°C for 3-5 hours to obtain a composite chain extender.

[0030] In the above reaction process, the rigid compound has an ester group and the ethanolamine has an amine group. The ester group in the rigid compound can combine with the amino group in the ethanolamine, and the ethanolamine and the rigid compound are combined together to finally obtain a composite chain extender.

[0031] Furthermore, the mass ratio of the rigid compound, methanol and ethanolamine is 0.9-1.1:15-20:0.7-0.8.

[0032] Furthermore, the rigid compound is composed of methyl 2,5-thiophenedicarboxylate and dimethyl 2,5-furandicarboxylate mixed in a mass ratio of 0.7-0.8:0.3-0.4.

[0033] A method for preparing a high-performance popcorn insole material comprises the following steps: The single-component polyurethane glue and popcorn particles are mixed and stirred evenly, and then injected into a sheet insole mold at 35-40° C., and after aging for 3-7 minutes, the mold is opened and cut to obtain a high-performance popcorn insole material.

[0034] Furthermore, the mass ratio of the one-component polyurethane glue to the popcorn particles is 2-3:7-8.

[0035] Beneficial effects of the present invention: (1) In the technical scheme of the present invention, a composite is obtained by combining a bio-based compound with a silanized nanomaterial; the bio-based compound is composed of a mixture of castor oil and vanillin. Castor oil can not only be used as a bio-based polyol to improve its reactivity with isocyanate and improve the crosslinking degree of polyurethane, but also act as a plasticizer to further enhance the hardness, flexibility and elasticity of polyurethane. Vanillin has good antioxidant properties and the aldehyde groups it contains can provide reaction sites for subsequent reactions. Mixing vanillin with castor oil can play a synergistic role and better improve the mechanical properties, wear resistance and durability of polyurethane; the silanized nanomaterial is prepared by combining a silane coupling agent with a nanomaterial; the nanomaterial is composed of hollow nanoparticles. The hollow nano titanium dioxide microspheres and nano silicon dioxide can play a synergistic role, effectively improving the air permeability, water permeability, wear resistance and mechanical properties of polyurethane. The silane coupling agent N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 3-isocyanatepropyltriethoxysilane are mixed, which can not only enhance the dispersibility of nanomaterials and improve their compatibility with polyurethane, but also improve the binding force between nanomaterials and polycaprolactone triol. Combining bio-based compounds with silanized nanomaterials can form a Schiff base structure, enhance the network rigidity and crosslinking density of polyurethane, thereby further improving the mechanical properties, wear resistance, air permeability and water permeability of polyurethane.

[0036] (2) In the technical scheme of the present invention, the complex is combined with a cross-linking agent to obtain a modified bio-based polyol; the cross-linking agent is composed of a mixture of 1-thioglycerol and 6-mercapto-1-hexanol, both of which have good binding force with the complex, and increase the number of hydroxyl groups on the complex, further improve the reaction activity between the modified bio-based polyol and isocyanate, and improve the cross-linking degree of polyurethane, so that the polyurethane has better mechanical properties, air permeability, water permeability and wear resistance.

[0037] (3) In the technical scheme of the present invention, isocyanate, modified bio-based polyol, polycaprolactone triol, catalyst and antioxidant are mixed to obtain a single-component polyurethane glue; polycaprolactone triol can improve the air permeability and mechanical properties of polyurethane; isocyanate is a mixture of isophorone diisocyanate, triphenylmethane triisocyanate and 4,4-diisocyanate dicyclohexylmethane, which improves the binding force between it and modified bio-based polyol and polycaprolactone triol, and improves the crosslinking density and mechanical properties of polyurethane; the composite chain extender is prepared by combining a rigid compound with ethanolamine; The rigid compound is composed of a mixture of methyl 2,5-thiophenedicarboxylate and dimethyl 2,5-furandicarboxylate, which have good binding force with ethanolamine. The formed composite chain extender can effectively improve the bonding strength of polyurethane, and has good reactivity with isocyanate, thereby improving the cross-linking degree of polyurethane, and further enhancing the bonding properties, mechanical properties, wear resistance, etc. of the single-component polyurethane glue; the single-component polyurethane glue is combined with popcorn particles to finally obtain a high-performance popcorn insole material with good air permeability, water permeability, wear resistance, mechanical properties and bonding properties.

[0038] (4) In the technical scheme of the present invention, a bio-based compound is combined with a silanized nanomaterial and then combined with a cross-linking agent to obtain a modified bio-based polyol; isocyanate, modified bio-based polyol, polycaprolactone triol, a catalyst, and an antioxidant are mixed to obtain a single-component polyurethane glue; the single-component polyurethane glue is combined with popcorn particles to finally obtain a high-performance popcorn insole material; the single-component polyurethane glue has a strong binding force with the popcorn particles, so that the prepared high-performance popcorn insole material not only has good air permeability, water permeability, wear resistance and mechanical properties, but also has good environmental protection, thereby expanding its application range and having good overall comprehensive performance. DETAILED DESCRIPTION

[0039] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The specific parameters of the raw materials used in the present invention are as follows: Castor oil (CAS No. 8001-79-4), vanillin (CAS No. 121-33-5), polycaprolactone triol (CAS No. 37625-56-2), isophorone diisocyanate (CAS No. 4098-71-9), 4,4-diisocyanate dicyclohexylmethane (CAS No. 5124-30-1), 1-thioglycerol (CAS No. 96-27-5), 6-mercapto-1-hexanol (CAS No. 1633-78-9), 2,5-thiophenedicarboxylic acid Ester (CAS No.: 4282-34-2), dimethyl 2,5-furandicarboxylate (CAS No.: 4282-32-0), all of the above materials were provided by Shanghai MacLean Biochemical Technology Co., Ltd.; triphenylmethane triisocyanate, CAS: 2422-91-5, was provided by Shanghai Yien Chemical Technology Co., Ltd.; nano-silica: particle size 30-50nm, was provided by Wuhu Xinda New Material Technology Co., Ltd.; popcorn particles: thermoplastic polyurethane elastomer, was provided by Changzhou Shuncheng Polymer Materials Co., Ltd.

[0041] The raw materials used in the following examples and comparative examples, the preparation method of hollow nano titanium dioxide microspheres comprises the following steps: According to the mass ratio of potassium chloride aqueous solution, ethanol and butyl titanate being 4:97:2.5, 0.4 mol / L potassium chloride aqueous solution was added to ethanol, and then butyl titanate was added, and stirred for 12 minutes, allowed to stand at room temperature for 22 hours, washed with anhydrous ethanol and deionized water three times each (the mass of anhydrous ethanol each time was 5 times the mass of butyl titanate, and the mass of deionized water each time was 8 times the mass of butyl titanate), and dried at 45°C for 24 hours to obtain solid nano-titanium dioxide. According to the mass ratio of solid nano-titanium dioxide, ammonium fluoride and deionized water being 0.22:0.1:38, solid nano-titanium dioxide and ammonium fluoride were added to deionized water, stirred evenly, reacted at 180°C for 12 hours, filtered, washed with anhydrous ethanol and deionized water three times each (the mass of anhydrous ethanol each time was 10 times the mass of ammonium fluoride, and the mass of deionized water each time was 15 times the mass of ammonium fluoride), and finally dried at 45°C for 24 hours to obtain hollow nano-titanium dioxide microspheres.

[0042] Example 1 Preparation of one-component polyurethane glue, the specific steps are: A1: According to the mass ratio of bio-based compound to ethanol of 0.8:30, the bio-based compound was added to ethanol to obtain solution A, according to the mass ratio of silanized nanomaterial to ethanol of 0.9:25, the silanized nanomaterial was added to ethanol to obtain solution B, according to the mass ratio of solution A to solution B of 2:1, solution B was added to solution A, and then stirred at 45°C for 7 hours. After the reaction, it was cooled to room temperature, filtered, washed with ethanol 3 times (the mass of ethanol each time was 15 times the mass of silanized nanomaterial), and vacuum dried at 60°C for 24 hours to obtain a composite, wherein the bio-based compound is composed of castor oil and vanillin mixed at a mass ratio of 1:0.6; The preparation method of silanized nanomaterials comprises the following steps: According to the mass ratio of ethanol, deionized water and silane coupling agent being 70:8:19, ethanol and deionized water are mixed, silane coupling agent is added, and stirred evenly, acetic acid is added, and stirred until the pH value of the solution reaches 3, and then ultrasonic treatment is performed for 25 minutes (ultrasonic power is 300W, ultrasonic frequency is 40kHz), nanomaterials (the mass of nanomaterials is 50% of the mass of silane coupling agent) are added, and stirred for reaction at 50°C for 11 hours. After the reaction is completed, it is washed with ethanol 3 times (the mass of ethanol each time is 1.5 times the mass of deionized water), and dried at 50°C for 4 hours to obtain silanized nanomaterials, wherein the silane coupling agent is composed of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 3-isocyanatepropyltriethoxysilane mixed in a mass ratio of 0.8:0.4; the nanomaterial is composed of hollow nano titanium dioxide microspheres and nano silicon dioxide mixed in a mass ratio of 0.9:0.5; A2: According to the mass ratio of the composite, the cross-linking agent and the photoinitiator 1173 being 0.8:2.8:0.03, the composite and the cross-linking agent are mixed, and then the photoinitiator 1173 is added and stirred evenly, and then the mixture is irradiated with ultraviolet light of a mercury lamp in an ice water bath at 0°C for 1 hour (the power of the mercury lamp is 50W). After the irradiation, ethyl acetate is added for dilution (the mass of ethyl acetate is 10 times the mass of the composite), and then washed with deionized water and saturated sodium chloride solution 5 times each (the mass of deionized water each time is 12 times the mass of the composite, and the mass of saturated sodium chloride solution each time is 15 times the mass of the composite), and then dried with magnesium sulfate, and the ethyl acetate is removed by rotary evaporation, and finally vacuum dried at 50°C overnight to obtain a modified bio-based polyol, wherein the cross-linking agent is composed of 1-thioglycerol and 6-mercapto-1-hexanol mixed in a mass ratio of 0.8:0.3; A one-component polyurethane glue comprises the following raw materials in parts by weight: 35 parts of modified bio-based polyol, 20 parts of polycaprolactone triol, 10 parts of composite chain extender, 20 parts of isocyanate, 0.05 parts of stannous isooctanoate and 1 part of antioxidant 1076; The preparation method comprises the following steps: Weigh the raw materials by mass, put the modified bio-based polyol, polycaprolactone triol and composite chain extender into a reactor, heat to 120°C, vacuum dehydrate under stirring, then cool to 70°C, add isocyanate, react at 70°C for 2h, add stannous isooctanoate and antioxidant 1076 under nitrogen protection, continue to react at 70°C for 0.5h, vacuum degassing until no bubbles appear, discharge, and obtain a one-component polyurethane glue, wherein the isocyanate is a mixture of isophorone diisocyanate, triphenylmethane triisocyanate and 4,4-diisocyanate dicyclohexylmethane in a mass ratio of 1:0.6:0.2; The preparation method of the composite chain extender comprises the following steps: According to the mass ratio of the rigid compound, methanol and ethanolamine being 0.9:15:0.7, the rigid compound is added to methanol, and then ethanolamine is added, and then the reaction is stirred at 45°C for 7 hours. After the reaction is completed, the methanol is removed by rotary evaporation, and the mixture is washed with acetone for 3 times (the mass of acetone each time is 80% of the mass of methanol), and then filtered, and finally dried at 70°C for 3 hours to obtain a composite chain extender, wherein the rigid compound is composed of methyl 2,5-thiophenedicarboxylate and dimethyl 2,5-furandicarboxylate mixed in a mass ratio of 0.7:0.3; A high-performance popcorn insole material, comprising a single-component polyurethane glue and popcorn particles; The preparation method comprises the following steps: According to the mass ratio of single-component polyurethane glue and popcorn particles being 2:7, the single-component polyurethane glue and popcorn particles are mixed, stirred evenly at a speed of 3000 rpm, and then injected into a sheet insole mold at 35°C. After aging for 3 minutes, the high-performance popcorn insole material is obtained through mold opening and cutting.

[0043] Example 2 Preparation of one-component polyurethane glue, the specific steps are: A1: According to the mass ratio of bio-based compound to ethanol of 1:35, the bio-based compound was added to ethanol to obtain solution A, according to the mass ratio of silanized nanomaterial to ethanol of 1:30, the silanized nanomaterial was added to ethanol to obtain solution B, according to the mass ratio of solution A to solution B of 2:1, solution B was added to solution A, and then stirred at 50°C for 8 hours. After the reaction, it was cooled to room temperature, filtered, washed with ethanol 3 times (the mass of ethanol each time was 15 times the mass of silanized nanomaterial), and vacuum dried at 65°C for 24 hours to obtain a composite, wherein the bio-based compound is composed of castor oil and vanillin mixed at a mass ratio of 1.1:0.65; The preparation method of silanized nanomaterials comprises the following steps: According to the mass ratio of ethanol, deionized water and silane coupling agent being 72:10:20, ethanol and deionized water are mixed, silane coupling agent is added, and stirred evenly, acetic acid is added, and stirred until the pH value of the solution reaches 3.5, and then ultrasonic treatment is performed for 30 minutes (ultrasonic power is 300W, ultrasonic frequency is 40kHz), nanomaterials (the mass of nanomaterials is 50% of the mass of silane coupling agent) are added, and stirred for reaction at 53°C for 12 hours. After the reaction is completed, it is washed with ethanol three times (the mass of ethanol each time is 1.5 times the mass of deionized water), and dried at 55°C for 5 hours to obtain silanized nanomaterials, wherein the silane coupling agent is composed of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 3-isocyanatepropyltriethoxysilane mixed in a mass ratio of 0.85:0.45; the nanomaterial is composed of hollow nano titanium dioxide microspheres and nano silicon dioxide mixed in a mass ratio of 1:0.55; A2: The composite material and the cross-linking agent were mixed according to the mass ratio of the composite material, the cross-linking agent and the photoinitiator 651 being 1:3:0.04, and the photoinitiator 651 was added and stirred evenly. The mixture was then irradiated with ultraviolet light from a mercury lamp for 1.5 h in an ice water bath at 2°C (the power of the mercury lamp was 50 W). After the irradiation, ethyl acetate was added for dilution (the mass of ethyl acetate was 10 times the mass of the composite material), and the mixture was washed with deionized water and saturated sodium chloride solution 5 times each (the mass of deionized water each time was 12 times the mass of the composite material, and the mass of saturated sodium chloride solution each time was 15 times the mass of the composite material), and then dried with magnesium sulfate, and the ethyl acetate was removed by rotary evaporation. Finally, the mixture was vacuum dried at 55°C overnight to obtain a modified bio-based polyol, wherein the cross-linking agent was composed of 1-thioglycerol and 6-mercapto-1-hexanol mixed in a mass ratio of 0.85:0.35; A one-component polyurethane glue comprises the following raw materials in parts by weight: 40 parts of modified bio-based polyol, 25 parts of polycaprolactone triol, 12 parts of composite chain extender, 22 parts of isocyanate, 0.08 parts of dibutyltin dilaurate and 2 parts of antioxidant 168; The preparation method comprises the following steps: Weigh the raw materials by mass, put the modified bio-based polyol, polycaprolactone triol and composite chain extender into a reaction kettle, heat to 125°C, vacuum dehydrate under stirring, then cool to 75°C, add isocyanate, react at 75°C for 2.5h, add dibutyltin dilaurate and antioxidant 168 under nitrogen protection, continue to react at 75°C for 1h, vacuum degassing until no bubbles appear, discharge the material, and obtain a one-component polyurethane glue, wherein the isocyanate is a mixture of isophorone diisocyanate, triphenylmethane triisocyanate and 4,4-diisocyanate dicyclohexylmethane in a mass ratio of 1.1:0.65:0.25; The preparation method of the composite chain extender comprises the following steps: According to the mass ratio of the rigid compound, methanol and ethanolamine being 1:18:0.75, the rigid compound is added to methanol, and then ethanolamine is added, and then stirred at 50°C for 8 hours. After the reaction is completed, the methanol is removed by rotary evaporation, washed with acetone for 3 times (the mass of acetone each time is 80% of the mass of methanol), filtered, and finally dried at 75°C for 4 hours to obtain a composite chain extender, wherein the rigid compound is composed of methyl 2,5-thiophenedicarboxylate and dimethyl 2,5-furandicarboxylate mixed in a mass ratio of 0.75:0.35; A high-performance popcorn insole material, comprising a single-component polyurethane glue and popcorn particles; The preparation method comprises the following steps: According to the mass ratio of single-component polyurethane glue and popcorn particles being 2.5:7.5, the single-component polyurethane glue and popcorn particles are mixed, stirred evenly at a speed of 3500rpm, and then injected into a sheet insole mold at 38°C. After aging for 5 minutes, the high-performance popcorn insole material is obtained through mold opening and cutting.

[0044] Example 3 Preparation of one-component polyurethane glue, the specific steps are: A1: According to the mass ratio of bio-based compound to ethanol of 1.2:40, the bio-based compound was added to ethanol to obtain solution A, according to the mass ratio of silanized nanomaterial to ethanol of 1.1:35, the silanized nanomaterial was added to ethanol to obtain solution B, according to the mass ratio of solution A to solution B of 2:1, solution B was added to solution A, and then stirred at 55°C for 9 hours. After the reaction, it was cooled to room temperature, filtered, washed with ethanol 3 times (the mass of ethanol each time was 15 times the mass of silanized nanomaterial), and vacuum dried at 70°C for 24 hours to obtain a composite, wherein the bio-based compound was composed of castor oil and vanillin mixed at a mass ratio of 1.2:0.7; The preparation method of silanized nanomaterials comprises the following steps: According to the mass ratio of ethanol, deionized water and silane coupling agent being 75:12:21, ethanol and deionized water are mixed, silane coupling agent is added, and stirred evenly, acetic acid is added, and stirred until the pH value of the solution reaches 4, and then ultrasonic treatment is performed for 35 minutes (ultrasonic power is 300W, ultrasonic frequency is 40kHz), nanomaterials (the mass of nanomaterials is 50% of the mass of silane coupling agent) are added, and stirred for reaction at 55°C for 13 hours. After the reaction is completed, it is washed with ethanol 3 times (the mass of ethanol each time is 1.5 times the mass of deionized water), and dried at 60°C for 6 hours to obtain silylated nanomaterials, wherein the silane coupling agent is composed of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 3-isocyanatepropyltriethoxysilane mixed in a mass ratio of 0.9:0.5; the nanomaterial is composed of hollow nano titanium dioxide microspheres and nano silicon dioxide mixed in a mass ratio of 1.1:0.6; A2: According to the mass ratio of the composite, the cross-linking agent and the photoinitiator 1173 being 1.2:3.2:0.05, the composite and the cross-linking agent were mixed, and then the photoinitiator 1173 was added and stirred evenly. Then, the mixture was irradiated with ultraviolet light of a mercury lamp for 2 hours in an ice water bath at 4°C (the power of the mercury lamp was 50W). After the irradiation, ethyl acetate was added for dilution (the mass of ethyl acetate was 10 times the mass of the composite), and the mixture was washed with deionized water and saturated sodium chloride solution 5 times each (the mass of deionized water each time was 12 times the mass of the composite, and the mass of saturated sodium chloride solution each time was 15 times the mass of the composite), and then dried with magnesium sulfate, and the ethyl acetate was removed by rotary evaporation. Finally, the mixture was vacuum dried at 60°C overnight to obtain a modified bio-based polyol, wherein the cross-linking agent was composed of 1-thioglycerol and 6-mercapto-1-hexanol mixed in a mass ratio of 0.9:0.4; A one-component polyurethane glue comprises the following raw materials in parts by weight: 45 parts of modified bio-based polyol, 30 parts of polycaprolactone triol, 15 parts of composite chain extender, 25 parts of isocyanate, 0.1 parts of stannous isooctanoate and 3 parts of antioxidant 1010; The preparation method comprises the following steps: Weigh the raw materials by mass, put the modified bio-based polyol, polycaprolactone triol and composite chain extender into a reaction kettle, heat to 130°C, vacuum dehydrate under stirring, then cool to 80°C, add isocyanate, react at 80°C for 3h, add stannous isooctanoate and antioxidant 1010 under nitrogen protection, continue to react at 80°C for 1.5h, vacuum degassing until no bubbles appear, discharge, and obtain a one-component polyurethane glue, wherein the isocyanate is a mixture of isophorone diisocyanate, triphenylmethane triisocyanate and 4,4-diisocyanate dicyclohexylmethane in a mass ratio of 1.2:0.7:0.3; The preparation method of the composite chain extender comprises the following steps: According to the mass ratio of the rigid compound, methanol and ethanolamine being 1.1:20:0.8, the rigid compound is added to methanol, and then ethanolamine is added, and then the reaction is stirred at 55°C for 9 hours. After the reaction is completed, the methanol is removed by rotary evaporation, and the mixture is washed with acetone for 3 times (the mass of acetone each time is 80% of the mass of methanol), and then filtered, and finally dried at 80°C for 5 hours to obtain a composite chain extender, wherein the rigid compound is composed of methyl 2,5-thiophenedicarboxylate and dimethyl 2,5-furandicarboxylate mixed in a mass ratio of 0.8:0.4; A high-performance popcorn insole material, comprising a single-component polyurethane glue and popcorn particles; The preparation method comprises the following steps: According to the mass ratio of single-component polyurethane glue and popcorn particles being 3:8, the single-component polyurethane glue and popcorn particles are mixed, stirred evenly at a speed of 4000 rpm, and then injected into a sheet insole mold at 40°C. After aging for 7 minutes, the high-performance popcorn insole material is obtained through mold opening and cutting.

[0045] Comparative Example 1 The difference between this comparative example and Example 3 is that when preparing the one-component polyurethane glue, in step A1, the mass of the bio-based compound is replaced by castor oil, and the remaining steps and raw materials are the same as those in Example 3; A1: According to the mass ratio of castor oil to ethanol of 1.2:40, castor oil was added to ethanol to obtain solution A, according to the mass ratio of silylated nanomaterial to ethanol of 1.1:35, silylated nanomaterial was added to ethanol to obtain solution B, according to the mass ratio of solution A to solution B of 2:1, solution B was added to solution A, and then stirred for reaction at 55°C for 9 hours. After the reaction, it was cooled to room temperature, filtered, washed with ethanol 3 times (the mass of ethanol each time was 15 times the mass of silylated nanomaterial), and vacuum dried at 70°C for 24 hours to obtain a composite.

[0046] Comparative Example 2 The difference between this comparative example and Example 3 is that when preparing the one-component polyurethane glue, in step A1, the mass of the bio-based compound is replaced by vanillin, and the remaining steps and raw materials are the same as those in Example 3; A1: Vanillin was added to ethanol at a mass ratio of 1.2:40 to obtain solution A. Silylated nanomaterials were added to ethanol at a mass ratio of 1.1:35 to obtain solution B. Solution B was added to solution A at a mass ratio of 2:1 to solution B. The mixture was stirred and reacted at 55°C for 9 hours. After the reaction, the mixture was cooled to room temperature, filtered, washed with ethanol for 3 times (the mass of ethanol each time was 15 times the mass of the silanized nanomaterial), and vacuum dried at 70°C for 24 hours to obtain a composite.

[0047] Comparative Example 3 The difference between this comparative example and Example 3 is that when preparing the one-component polyurethane glue, in step A2, the mass of the cross-linking agent is replaced by 1-thioglycerol, and the remaining steps and raw materials are the same as those in Example 3; A2: According to the mass ratio of the complex, 1-thioglycerol and photoinitiator 1173 of 1.2:3.2:0.05, the complex and 1-thioglycerol were mixed, and then the photoinitiator 1173 was added and stirred evenly. Then, the mixture was irradiated with ultraviolet light of a mercury lamp for 2 h in an ice water bath at 4°C (the power of the mercury lamp was 50 W). After the irradiation, ethyl acetate was added for dilution (the mass of ethyl acetate was 10 times the mass of the complex), and the mixture was washed with deionized water and saturated sodium chloride solution for 5 times each (the mass of deionized water each time was 12 times the mass of the complex, and the mass of saturated sodium chloride solution each time was 15 times the mass of the complex), and then dried with magnesium sulfate, the ethyl acetate was removed by rotary evaporation, and finally vacuum dried at 60°C overnight to obtain a modified bio-based polyol.

[0048] Comparative Example 4 The difference between this comparative example and Example 3 is that when preparing the one-component polyurethane glue, in step A2, the mass of the crosslinking agent is replaced by 6-mercapto-1-hexanol, and the remaining steps and raw materials are the same as those in Example 3; A2: According to the mass ratio of the composite, 6-mercapto-1-hexanol and photoinitiator 1173 of 1.2:3.2:0.05, the composite and 6-mercapto-1-hexanol were mixed, and then the photoinitiator 1173 was added and stirred evenly. Then, the mixture was irradiated with ultraviolet light of a mercury lamp for 2 h in an ice water bath at 4°C (the power of the mercury lamp was 50 W). After the irradiation, ethyl acetate was added for dilution (the mass of ethyl acetate was 10 times the mass of the composite), and the mixture was washed with deionized water and saturated sodium chloride solution for 5 times each (the mass of deionized water each time was 12 times the mass of the composite, and the mass of saturated sodium chloride solution each time was 15 times the mass of the composite), and then dried with magnesium sulfate, the ethyl acetate was removed by rotary evaporation, and finally vacuum dried at 60°C overnight to obtain a modified bio-based polyol.

[0049] Comparative Example 5 The difference between this comparative example and Example 3 is that when preparing the one-component polyurethane glue, the isocyanate is composed of isophorone diisocyanate and triphenylmethane triisocyanate mixed in a mass ratio of 1.2:1, and the remaining steps and raw materials are the same as those in Example 3; The preparation method of one-component polyurethane glue comprises the following steps: Weigh the raw materials by mass, put the modified bio-based polyol, polycaprolactone triol and composite chain extender into the reactor, heat to 130°C, dehydrate under vacuum with stirring, then cool to 80°C, add isocyanate, react at 80°C for 3 hours, add stannous isooctanoate and antioxidant 1010 under nitrogen protection, continue to react at 80°C for 1.5 hours, vacuum degassing until no bubbles appear, discharge the material, and obtain a one-component polyurethane glue, wherein the isocyanate is a mixture of isophorone diisocyanate and triphenylmethane triisocyanate in a mass ratio of 1.2:1.

[0050] Comparative Example 6 The difference between this comparative example and Example 3 is that when preparing the one-component polyurethane glue, the mass of the rigid compound in the composite chain extender is replaced by methyl 2,5-thiophenedicarboxylate, and the remaining steps and raw materials are synchronized with Example 3; The preparation method of the composite chain extender comprises the following steps: According to the mass ratio of methyl 2,5-thiophenedicarboxylate, methanol and ethanolamine of 1.1:20:0.8, methyl 2,5-thiophenedicarboxylate was added to methanol, and then ethanolamine was added, and then stirred at 55°C for 9 hours. After the reaction was completed, methanol was removed by rotary evaporation, washed with acetone for 3 times (the mass of acetone each time was 80% of the mass of methanol), filtered, and finally dried at 80°C for 5 hours to obtain a composite chain extender.

[0051] Comparative Example 7 The difference between this comparative example and Example 3 is that when preparing the one-component polyurethane glue, the mass of the rigid compound in the composite chain extender is replaced by dimethyl 2,5-furandicarboxylate, and the remaining steps and raw materials are synchronized with Example 3; The preparation method of the composite chain extender comprises the following steps: According to the mass ratio of 2,5-furandicarboxylic acid dimethyl ester, methanol and ethanolamine being 1.1:20:0.8, 2,5-furandicarboxylic acid dimethyl ester was added to methanol, and then ethanolamine was added, and then stirred at 55°C for 9 hours. After the reaction was completed, methanol was removed by rotary evaporation, washed with acetone for 3 times (the mass of acetone each time was 80% of the mass of methanol), filtered, and finally dried at 80°C for 5 hours to obtain a composite chain extender.

[0052] Comparative Example 8 The difference between this comparative example and Example 3 is that when preparing the one-component polyurethane glue, the mass of polycaprolactone triol is replaced by modified bio-based polyol, and the remaining steps and raw materials are synchronized with Example 3; A one-component polyurethane glue comprises the following raw materials in parts by weight: 75 parts of modified bio-based polyol, 15 parts of composite chain extender, 25 parts of isocyanate, 0.1 parts of stannous isooctanoate and 3 parts of antioxidant 1010; The preparation method comprises the following steps: Weigh the raw materials by mass, put the modified bio-based polyol and the composite chain extender into the reactor, heat to 130°C, dehydrate under vacuum with stirring, then cool to 80°C, add isocyanate, react at 80°C for 3 hours, add stannous isooctanoate and antioxidant 1010 under nitrogen protection, continue to react at 80°C for 1.5 hours, vacuum degassing until no bubbles appear, discharge the material, and obtain a one-component polyurethane glue, wherein the isocyanate is a mixture of isophorone diisocyanate, triphenylmethane triisocyanate and 4,4-diisocyanate dicyclohexylmethane in a mass ratio of 1.2:0.7:0.3.

[0053] Comparative Example 9 The difference between this comparative example and Example 3 is that when preparing the one-component polyurethane glue, the modified bio-based polyol is replaced by polycaprolactone triol, and the remaining steps and raw materials are the same as those of Example 3; A one-component polyurethane glue comprises the following raw materials in parts by weight: 75 parts of polycaprolactone triol, 15 parts of a composite chain extender, 25 parts of isocyanate, 0.1 parts of stannous isooctanoate and 3 parts of an antioxidant 1010; The preparation method comprises the following steps: Weigh the raw materials by mass, put polycaprolactone triol and composite chain extender into a reactor, heat to 130°C, dehydrate under vacuum while stirring, then cool to 80°C, add isocyanate, react at 80°C for 3 hours, add stannous isooctanoate and antioxidant 1010 under nitrogen protection, continue to react at 80°C for 1.5 hours, vacuum degassing until no bubbles appear, discharge the material, and obtain a one-component polyurethane glue, wherein the isocyanate is a mixture of isophorone diisocyanate, triphenylmethane triisocyanate and 4,4-diisocyanate dicyclohexylmethane in a mass ratio of 1.2:0.7:0.3.

[0054] The high-performance popcorn insole materials prepared in Examples 1-3 and Comparative Examples 1-9 were tested for mechanical properties, air permeability, water vapor permeability and wear resistance; hardness test was performed according to GB / T 3903.4-2017, tensile strength and elongation test were performed according to GB / T 528-2009, and mechanical properties were characterized by hardness, tensile strength and elongation; air permeability test was performed according to GB / T 10655-2003; wear resistance test was performed according to GB / T 3903.2-2008; water vapor permeability test: the water vapor mass permeating vertically through the unit area of ​​the test sample under the condition of maintaining the specified temperature and humidity on both sides of the test sample within a certain period of time was expressed as [g / (m 2 .24h)] or [mg / (10cm 2.24h)] as the unit, set the test chamber conditions: temperature is (25±2)℃, relative humidity is (90±2)%, and the calculation formula is: WVT=(Δm-Δm0) / (A·t); WVT: moisture permeability [g / (m 2 .24h)]; Δm: difference between two weighings of the same test assembly (g); Δm0: difference between two weighings of the same test assembly of the blank sample (g); A: effective experimental area (m 2 ), in the present invention, it is 0.00283m 2 ; t: test time (h).

[0055] The test results are shown in Table 1 below: Table 1 Performance parameters of high performance popcorn insole materials prepared in Examples 1-3 and Comparative Examples 1-9

[0056] It can be seen from the data in Table 1 above that, by comparing Comparative Examples 1-2 with Example 3, it can be seen that the test results of the high-performance popcorn insole material prepared by replacing the mass of the bio-based compound with castor oil or vanillin are worse than those of Example 3, indicating that the bio-based compound composed of a mixture of castor oil and vanillin can play a synergistic role, improve the reactivity between the bio-based compound and the isocyanate, improve the crosslinking degree of the polyurethane, and better enhance the mechanical properties and wear resistance of the polyurethane, thereby further improving the air permeability, water permeability, wear resistance and mechanical properties of the popcorn insole material; By comparing Comparative Examples 3-5 with Example 3, it can be seen that the cross-linking agent is replaced with 1-thioglycerol or 6-mercapto-1-hexanol, or the isocyanate is a mixture of isophorone diisocyanate and triphenylmethane triisocyanate, and finally a high-performance popcorn insole material is prepared. The test results are worse than those of Example 3, indicating that the cross-linking agent composed of a mixture of 1-thioglycerol and 6-mercapto-1-hexanol not only has a good binding force with the composite, but also can enhance the binding force with the isocyanate, thereby improving the cross-linking degree of the polyurethane, further improving the mechanical properties, air permeability and water permeability of the polyurethane, and the isocyanate composed of a mixture of isophorone diisocyanate, triphenylmethane triisocyanate and 4,4-diisocyanate dicyclohexylmethane has a good binding force with the modified bio-based polyol and polycaprolactone triol, further improving the air permeability, water permeability, mechanical properties and wear resistance of the popcorn insole material; By comparing Comparative Examples 6-9 with Example 3, it can be seen that the high-performance popcorn insole material is prepared by replacing the mass of the rigid compound in the composite chain extender with methyl 2,5-thiophenedicarboxylate or dimethyl 2,5-furandicarboxylate, or replacing the mass of polycaprolactone triol with modified bio-based polyol, or replacing the mass of modified bio-based polyol with polycaprolactone triol. The test results are worse than those of Example 3, indicating that the rigid compound composed of a mixture of methyl 2,5-thiophenedicarboxylate and dimethyl 2,5-furandicarboxylate has a good binding force with ethanolamine, and the formed composite chain extender can effectively improve the bonding strength of polyurethane and increase the binding force between the single-component polyurethane glue and the popcorn particles; polycaprolactone triol and modified bio-based polyol have a good synergistic effect, which enhances its binding force with isocyanate, and further improves the air permeability, water permeability, wear resistance and mechanical properties of the popcorn insole material.

[0057] As can be seen from Table 1 above, the high-performance popcorn insole materials prepared in Examples 1-3 are compared with the high-performance popcorn insole materials prepared in Comparative Examples 1-9. The modified bio-based polyol is obtained by combining a bio-based compound with a silanized nanomaterial and then combining it with a cross-linking agent; isocyanate, modified bio-based polyol, polycaprolactone triol, a catalyst, and an antioxidant are mixed to obtain a one-component polyurethane glue; the one-component polyurethane glue is combined with popcorn particles to finally obtain a high-performance popcorn insole material, which meets the test performance requirements, while the high-performance popcorn insole materials prepared in Comparative Examples 1-9 do not meet the performance requirements. This shows that the high-performance popcorn insole material prepared by the present invention not only has good bonding performance, air permeability, water permeability, wear resistance and mechanical properties, but also has good environmental protection, which expands its application range.

[0058] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0059] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A high-performance popcorn insole material, characterized in that: Includes one-component polyurethane glue and popcorn particles; The one-component polyurethane glue comprises the following raw materials in parts by weight: 35-45 parts of modified bio-based polyol, 20-30 parts of polycaprolactone triol, 10-15 parts of composite chain extender, 20-25 parts of isocyanate, 0.05-0.1 parts of catalyst and 1-3 parts of antioxidant; The method for preparing the modified bio-based polyol comprises the following steps: A1: Combining bio-based compounds with silanized nanomaterials to obtain composites; A2: Combining the complex with a cross-linking agent to obtain a modified bio-based polyol.

2. The high-performance popcorn insole material according to claim 1, characterized in that: Step A1 is specifically as follows: The bio-based compound is added to ethanol to obtain solution A, the silanized nanomaterial is added to ethanol to obtain solution B, solution B is added to solution A, and then stirred and reacted at 45-55°C for 7-9h. After the reaction is completed, it is cooled to room temperature, filtered, washed with ethanol, and vacuum dried at 60-70°C to obtain a composite.

3. The high-performance popcorn insole material according to claim 2, characterized in that: The bio-based compound is composed of castor oil and vanillin mixed in a mass ratio of 1-1.2:0.6-0.

7.

4. The high-performance popcorn insole material according to claim 2, characterized in that: The preparation method of the silanized nanomaterial comprises the following steps: Mix ethanol and deionized water, add silane coupling agent, and stir evenly, then add acetic acid and stir until the pH value of the solution reaches 3-4, then perform ultrasonic treatment for 25-35 minutes, add nanomaterials, stir and react at 50-55°C for 11-13 hours, after the reaction is completed, wash with ethanol, and dry at 50-60°C for 4-6 hours to obtain silanized nanomaterials.

5. The high-performance popcorn insole material according to claim 4, characterized in that: The nano material is composed of hollow nano titanium dioxide microspheres and nano silicon dioxide mixed in a mass ratio of 0.9-1.1:0.5-0.

6.

6. The high-performance popcorn insole material according to claim 1, characterized in that: Step A2 is specifically as follows: The complex is mixed with a cross-linking agent, and a photoinitiator is added and stirred evenly. The mixture is then irradiated with ultraviolet light from a mercury lamp in an ice water bath for 1-2 hours. After the irradiation, ethyl acetate is added for dilution, and the mixture is washed with deionized water and a saturated sodium chloride solution in sequence, and then dried with magnesium sulfate. The ethyl acetate is removed by rotary evaporation, and finally vacuum dried at 50-60°C to obtain a modified bio-based polyol.

7. The high-performance popcorn insole material according to claim 6, characterized in that: The cross-linking agent is composed of 1-thioglycerol and 6-mercapto-1-hexanol mixed in a mass ratio of 0.8-0.9:0.3-0.

4.

8. The high-performance popcorn insole material according to claim 1, characterized in that: The preparation method of the one-component polyurethane glue comprises the following steps: Weigh the raw materials by mass, put the modified bio-based polyol, polycaprolactone triol and composite chain extender into the reaction kettle, heat to 120-130°C, vacuum dehydrate under stirring, then cool to 70-80°C, add isocyanate, react at 70-80°C for 2-3h, add catalyst and antioxidant under nitrogen protection, continue to react at 70-80°C for 0.5-1.5h, vacuum degassing until no bubbles appear, discharge the material, and obtain a one-component polyurethane glue.

9. The high-performance popcorn insole material according to claim 8, characterized in that: The preparation method of the composite chain extender comprises the following steps: The rigid compound is added to methanol, and then ethanolamine is added, and then the reaction is stirred at 45-55°C for 7-9 hours. After the reaction is completed, the methanol is removed by rotary evaporation, washed with acetone, filtered, and finally dried at 70-80°C for 3-5 hours to obtain a composite chain extender.

10. A method for preparing the high-performance popcorn insole material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The single-component polyurethane glue and popcorn particles are mixed and stirred evenly, and then injected into a sheet insole mold at 35-40° C., and after aging for 3-7 minutes, the mold is opened and cut to obtain a high-performance popcorn insole material.

Citation Information

Patent Citations

  • Vegetable oil-based self-repairing polymer based on Schiff base and preparation method and application thereof

    CN113004477A

  • Bio-based polyurethane composite material applied to insoles and preparation method of bio-based polyurethane composite material

    CN117164809A

  • High bio-based UV (ultraviolet) resin containing imine bonds as well as preparation method and application of high bio-based UV resin

    CN117603418A

  • Elastomer material for shoe sole and preparation method of elastomer material

    CN118165209A

  • Polyurethane hot melt adhesive for bonding and preparation method thereof

    CN118995117A